Perbandingan Implementasi Pendidikan Agama Islam Di Indonesia Dan Malaysia Dalam Penguatan Moderasi Beragama Siswa - Nurul Zahrah Hayati; Rifky Nur Hidayat; M. Hijra Adha; Syakinah Syakinah (Universitas Pakuan, 2026)
COMPARISON OF THE IMPLEMENTATION OF ISLAMIC RELIGIOUS EDUCATION IN INDONESIA AND MALAYSIA IN STRENGTHENING STUDENTS' RELIGIOUS MODERATION This study compares the implementation of Islamic Religious Education (PAI) in Indonesia and Malaysia in strengthening students' religious moderation. The background of this study is based on the important role of religious education in shaping moderate, tolerant, and inclusive attitudes in an increasingly diverse society and the challenges of globalization that have the potential to give rise to exclusive and extreme attitudes in religion. This study aims to analyze and compare how the two countries implement Islamic Religious Education in strengthening the values ​​of religious moderation in the school environment. The research method used is a qualitative study with a comparative study approach. Data collection techniques were carried out through documentation studies by reviewing various sources such as scientific journals, books, and educational policy documents in Indonesia and Malaysia. Data analysis was carried out using content analysis techniques through the stages of data reduction, data presentation, and drawing conclusions. The results show that the implementation of PAI in Indonesia uses an integrative approach that combines the value of moderation explicitly in the curriculum and contextualized learning with students' social realities. Meanwhile, in Malaysia, Islamic Education emphasizes a more centralized structural approach through the national curriculum, where the value of moderation is internalized through habituation, teacher role models, and a uniform education system. Both approaches contribute to the formation of moderate student character, although with different strategies.